2015
DOI: 10.1213/ane.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Regional Versus General Anesthesia in Surgical Patients with Chronic Obstructive Pulmonary Disease

Abstract: The use of regional anesthesia in patients with COPD is associated with lower incidences of composite morbidity, pneumonia, prolonged ventilator dependence, and unplanned postoperative intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(65 citation statements)
references
References 14 publications
2
61
2
Order By: Relevance
“… 32 Meta-analysis has demonstrated that regional anaesthesia may protect against development of postoperative pulmonary complications in patients with chronic respiratory diseases. 33 Similarly, a multicentre randomised controlled trial recently reported that regional anaesthesia and analgesia using paravertebral block reduced the risk of postoperative pulmonary complications but not recurrence or mortality in breast cancer after curative surgery compared with systemic opioid therapy. 34 …”
Section: Discussionmentioning
confidence: 98%
“… 32 Meta-analysis has demonstrated that regional anaesthesia may protect against development of postoperative pulmonary complications in patients with chronic respiratory diseases. 33 Similarly, a multicentre randomised controlled trial recently reported that regional anaesthesia and analgesia using paravertebral block reduced the risk of postoperative pulmonary complications but not recurrence or mortality in breast cancer after curative surgery compared with systemic opioid therapy. 34 …”
Section: Discussionmentioning
confidence: 98%
“…Other studies in the literature also appear to support Paskins's results. Hausman et al [16] performed a study to quantify the benefit of avoiding GA in COPD patients. For this purpose, 2644 "regional" COPD patients (i.e., surgery performed under spinal, epidural or peripheral nerve block anaesthetic techniques) were propensity-score matched to COPD patients who underwent GA and invasive mechanical ventilation.…”
Section: General Anaesthesia and Neuraxial Anaesthesia: Effects On Lumentioning
confidence: 99%
“…These effects could negate the potential benefits of avoiding intraoperative endotracheal intubation and mechanical ventilation [16]. Since NIV can (1) partially compensate for the affected respiratory function by unloading the respiratory muscles and reducing the work of breathing, (2) improve alveolar recruitment with preservation of lung volumes, resulting in better gas exchange, (3) reduce right ventricular preload and left ventricular afterload, and (4) avoid complications of invasive mechanical ventilation [35][36][37][38][39][40], the intraoperative use of NIV along with NA may be, at least in theory, justifiable in some patients with COPD or chest wall and NMDs (Figure 1).…”
Section: Non-invasive Ventilation To Support Lung Function During Neumentioning
confidence: 99%
“…Compared with general anesthesia (GA), regional anesthesia can provide more stable hemodynamics and effective opioid-free analgesia [4]. It is also associated with relatively lower incidence of perioperative complications, shorter postoperative stays and greater patient satisfaction [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%